IMPLEMENTASI PROFIL PELAJAR PANCASILA DALAM PENDIDIKAN KARAKTER SEBAGAI KONKRETISASI IDENTITAS BANGSA INDONESIA DI SDN 205 KOTA JAMBI - Mustakim, Adimas; Airin, Airin; Damanik, Dearni Christiany; Julianty, Ella Putri; Asdah, Fhitria Sheptiana (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
This research discusses the implementation of the Pancasila student profile in character education as a concretization of the identity of the Indonesian nation. This research was conducted in class V of SD Negeri 205 Jambi City. This research uses a qualitative research approach with the type of phenomenological research, using three methods in data collection, namely observation, interviews and document study. The results of this research show that the Pancasila student profile is a formulation of national education ideals based on character education, the abilities expected in this Pancasila student profile include having noble character, independence, critical reasoning, creativity, mutual cooperation and global diversity. . Indonesian students must cultivate these six dimensions of character as an effort to strengthen the concretization of the identity of the Indonesian nation.